Engineering supramolecular helical assemblies via interplay between carbon(sp) tetrel and halogen bonding interactions. Issue 16 (11th April 2023) - Dedeoglu, Burcu; Gürek, Ayşe Gül; Zorlu, Yunus; Ayhan, Mehmet Menaf
Abstract : Building supramolecular helical structures is a challenge due to difficulties in the design and control of competitive noncovalent forces. Abstract : Building supramolecular helical structures is a challenge due to difficulties in the design and control of competitive noncovalent forces. Herein, we report three scaffolds (1a, 1b, and 1c ) decorated with –CN and –Br groups. These groups known for their ability to form multiple noncovalent interactions and with efficient design can be utilized to achieve such complex structures. X-Ray analyses revealed that the crystal packing of 1a, 1b and 1c is dominated by highly directional Br⋯CN Csp -tetrel bonding (1a ), Br⋯π, Br⋯N (1b ) and Br⋯Br (1c ) XB interactions, and these interactions have led to the formation of achiral P / M, chiral M and achiral P / M helical assemblies, respectively. A detailed structural and computational analysis was performed to clarify the nature and estimate the strength of these interactions in helical assemblies. MEP analyses of 1a, 1b, and 1c have shown that the potential of electron-deficient and electron-rich regions within the structures has similar values. Yet, the geometric accessibility of σ-holes has differed with each scaffold. Thus, dominant interactions have changed and consequently led to different helical assembly formations. The interaction energies are around −11.4 (1a ), −4.0 (1b ), and −4.6 (1c ) kcal mol −1 and mainly driven by dispersion, followed by electrostatic interactions. To our surprise, the Csp -tetrel bonding (1a ), considered the weakest among non-covalent interactions, is the strongest interaction among the three scaffolds, which shows the importance of accessibility of Sigma holes. These findings are expected to contribute to the future rational design of complex self-assembled materials, utilizing Csp -tetrel and XB interactions, in various applications such as crystal engineering, organic semiconductors, sensor devices, and medicinal chemistry.